133 One versus two prostaglandin F2α injections on progesterone concentrations and luteolysis in suckling beef cows subjected to a 5-day controlled internal drug release-Cosynch protocol. (7th December 2018) - Spencer, J; Menegatti Zoca, S; Reynolds, M; Price, W; Shafii, B; Ahmadzadeh, A
Abstract: The objective was to examine the effects of one or two doses of conventional prostaglandin F2α (PG ), or one high-concentration PG (HighCon ) on progesterone (P 4 ) concentrations and luteolysis (P4 <0.5 ng/mL) in suckling beef cows subjected to a 5-d CIDR-Cosynch protocol. On d 0, 54 cows received GnRH (100µg), and a CIDR was inserted. On d 5, the CIDR was removed and cows were assigned randomly to receive either one dose of PG (1PG ; 25mg; n=19), two doses of PG 12 h apart (2PG ; n=17; 25mg/dose), or one HighCon PG dose (25mg; n=18). On d 5, beginning one h after CIDR removal, blood samples were collected every 12 h from d 5–8 to measure P4 concentrations. On d 8, cows received a second GnRH injection and were inseminated. Ovaries were examined by ultrasonography on d 0, 5 and 8. A repeated measures, generalized linear model was used to determine differences in P4 concentrations. The P4 data were assumed to follow a lognormal distribution and the model included fixed effects for treatment, time, time by treatment interaction, and a random effect of cows. On d 5, all cows had elevated P4 concentrations and luteal tissue. Serum P4 concentrations decreased over time in all treatments ( P< 0.01). There were no treatment effects ( P >0.1). There was a treatment by time interaction effect on P4 . Serum P4 concentrations at 72 h after treatment tended ( P =0.09) to differ and averaged 0.50, 0.18, and 0.25 ng/mL for 1PG, 2PG, and HighCon, respectively, and were ≤0.5 ng/mL in all treatments. The proportion of cows that went through luteolysis (P4 <0.5 ng/mL) tended to be greater ( P =0.09) in 2PG and HighCon compared with to 1PG (89, 88, and 63%, respectively). One dose of HighCon is as effective as 2PG in causing luteolysis by the time of AI in suckling beef cows.